2017
DOI: 10.1007/s10457-017-0172-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrating local knowledge with tree diversity analyses to optimize on-farm tree species composition for ecosystem service delivery in coffee agroforestry systems of Uganda

Abstract: Coffee agroforestry systems deliver ecosystem services (ES) critical for rural livelihoods like food but also disservices that constrain livelihoods like fostering coffee-pests. Since such ES are treebased, maximizing ES and limiting constraints requires knowledge on optimizing on-farm tree composition especially trees adapted to local conditions. The study was in three sites along a rainfall gradient in Central Uganda where we: assessed tree diversity in coffee agroforestry; ranked tree suitability for provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
2
15
1
Order By: Relevance
“…Kilimanjaro. Similar studies have been conducted in other East African countries and the differences in findings [15,16,24,25] demonstrate the importance of locally specific investigations.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Kilimanjaro. Similar studies have been conducted in other East African countries and the differences in findings [15,16,24,25] demonstrate the importance of locally specific investigations.…”
Section: Introductionsupporting
confidence: 73%
“…Some other studies also show the importance of shade tree species for coffee production is matched with their planting densities [36,42]. Bukomenko, et al [24], however, found a mismatch between ESs that are important for respondents and the trees they have on their fields. Graefe, et al [30] used a similar methodology for cocoa production in Ghana and also reported disparities between higher ranked tree species suitable for cocoa intercropping and their abundance in the northern part of the cocoa belt with marginal conditions for cocoa production.…”
Section: Highly Ranked Tree Speciesmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, removing A. chinensis from coffee plots and increasing the density of sap exuding trees should reduce X. compactus infestations, although this is not without caution: removing one host to a generalist pest such as X. compactus , which thrives on many hosts, may not significantly affect their population (Ratnadass et al ., ). Nonetheless, farmers choosing to eliminate A. chinensis should aim to replace it with suitable trees that provide similar ecosystem services and preferably exude sap (Bukomeko, ).…”
Section: Discussionmentioning
confidence: 99%